Sistem Pendukung Keputusan untuk Pemutusan Hubungan Kerja Karyawan Menggunakan Metode Elimination and Choice Translation Reality - Mesran Mesran; Rusiana Rusiana; Maringan Sianturi (Jurnal Teknologi dan Sistem Komputer, 2018)
This study aims to develop a decision support system in determining employees which will be laid off. The data used in the research sourced from PT. Mitra Andal Sejati Medan in 2017. This study used the ELECTRE method to conduct an assessment of company employees. The criteria used in the research were absence (C1), appearance (C2), performance (C3), and sales volume (C4). This ELECTRE system can provide an effective decision for termination of employment based on lowest employee rank.